2019
DOI: 10.3389/fcimb.2019.00110
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Bacteriocin-Related Typing of Streptococcus dentisani

Abstract: Streptococcus oralis subspecies dentisani is explored as an anti-cariogenic probiotic. Here, subjecting freshly stimulated saliva samples of 35 healthy volunteers, six epidemiologically unrelated and two related strains were isolated (prevalence around 20%) applying a newly developed three-step procedure. Furthermore, the probiotic strain S. dentisani 7746 (AB-Dentisanium®) was tested under a variety of environmental conditions for its inhibitory effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 43 publications
2
33
0
Order By: Relevance
“…Among them are Firmicutes , including streptococci and lactobacilli, the most promising candidates. Recently, we have published about the in vitro anti-cariogenic potential of Streptococcus oralis subspecies dentisani 7746 in comparison to other probiotic strains or combinations of strains [ 15 ]. Here, we explored the in vitro anti-periodontitis potential of this species in comparison to Streptococcus salivarius subsp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them are Firmicutes , including streptococci and lactobacilli, the most promising candidates. Recently, we have published about the in vitro anti-cariogenic potential of Streptococcus oralis subspecies dentisani 7746 in comparison to other probiotic strains or combinations of strains [ 15 ]. Here, we explored the in vitro anti-periodontitis potential of this species in comparison to Streptococcus salivarius subsp.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that S . dentisani 7746 produces about ten different bacteriocins [ 15 ]. Combined with the plasmid-encoded salivaricin-variants A2, B, 9, and MPS produced by K12 and M18 [ 33 ], as well as bacteriocin immunity factors, a concerted activity directed against the pathogens is needed avoiding a friendly fire of against the co-producer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we propose that future work aims to identify the specific bacteriocins which are responsible for the inhibition of this major human pathogen. On the other hand, a potentially negative effect of the S. dentisani strain 7746 bacteriocins effect is their inhibitory action against other S. dentisani strains (Conrads et al, 2018 , 2019 ). Thus, although our data show an increase in S. dentisani levels after the administration of the probiotic, this could be so at the expense of a reduction in the indigenous population of this species.…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus dentisani was first isolated in 2011 from caries-free individuals where a metagenomic analysis of dental plaque samples had shown an over-representation of genes coding for antimicrobial peptides (Belda-Ferre et al, 2012 ). In fact, at least 11 bacteriocins have been described in this organism based on bioinformatic analysis (Conrads et al, 2019 ) and has been shown to inhibit different oral pathogens ranging from Fusobacterium nucleatum to Porphyromonas gingivalis or Streptococcus mutans (López-López et al, 2017 ; Esteban-Fernández et al, 2019 ; Llena et al, 2019 ). Genomic and physiological analysis determined that this bacterium represented a new species (Benítez-Páez et al, 2014 ) although its potential assignment as a subspecies of S. oralis is under debate (Jensen et al, 2016 ; Velsko et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%